Hubungan Pengetahuan, Sikap dan Peran Orangtua terhadap Praktik Kesehatan Reproduksi Remaja pada Pelajar SMP Negeri 16 Kupang - Chandra Yudit Fora; Yuliana Radja Riwu; Amelya Sir (Universitas Nusa Cendana, 2021)
Adolescence is a period of transitional development between childhood and adulthood where adolescents are vulnerable to peer influence in terms of interests, attitudes, appearances, and behaviors. This vulnerability may lead to various issues including reproductive health problems. The incidence of adolescent reproductive health problems such as early pregnancy and childbirth, unsafe abortion, sexually transmitted infections including Human Immunodeficiency Virus, sexual harassment/rape is influenced by factors of knowledge, attitudes, and the role of parents. The purpose of this study was to analyze factors related to reproductive health practices at SMP Negeri 16 Kupang. This research was an analytic observational study with a cross-sectional approach. The sample consisted of 155 adolescents. The study was conducted in August 2020. Data analysis in this study used simple logistic regression analysis. The results found that 52.9% of adolescents had poor reproductive health practices. Reproductive health practice was associated with knowledge (p = 0.000), and the role of parents (p = 0.048) while attitudes (p = 0.948) was found unrelated to the practice. Increasing understanding of the importance of maintaining reproductive health is necessary to help adolescents anticipate the impact of reproductive health problems.